Induced Coherence via Spontaneous Four‐Wave Mixing in Atomic Ensembles. Issue 8 (4th June 2021) - Park, Jiho; Kim, Heonoh; Moon, Han Seb
Abstract: Induced coherence was first demonstrated three decades ago in a proof‐of‐principle experiment using entangled photons from spontaneous parametric down‐conversion in nonlinear crystals. This phenomenon is considered an interesting instance of complementarity, which lies at the heart of quantum optics. Here, the first demonstration of induced coherence across two coupled interferometers based on spontaneous four‐wave mixing (SFWM) in two independent hot‐atomic‐vapor‐based entangled photon sources is reported. When both the pump and coupling lasers are split and interact with two warm 87 Rb atomic ensembles, single‐photon interference is observed between the two idler photons of the narrowband photon pairs, generated via SFWM from the two cascade‐type atomic systems. Furthermore, it is found that the phase memory effect arises from the phase of the bidirectional counter‐propagating pump and coupling lasers, respectively. This work takes an important step toward the transition to the era of quantum optics being driven by atomic ensembles from solid‐state systems. Abstract : The demonstration of induced coherence based on spontaneous four‐wave mixing in two independent hot‐atomic‐vapor‐based entangled photon sources is reported for the first time. Because of long coherence length of the photons emitted from atomic ensemble, the single‐photon and two‐photon interferences of the photons with induced coherence can be observed at a path‐length difference of 0.5 m.